Moving out of poverty a brief review of the process of inclusive growth in Lao People’s Democratic Republic - Estudillo, Jonna (Philippine Review of Economics, 2017)
Using a nationally representative data set, this review presents spatial features of poverty in Lao People’s Democratic Republic during its rapid economic growth between 2002 and 2012. We found that although the benefits of rapid economic growth have reached a large segment of the population, these have not flowed uniformly across population groups. The poor have benefitted, but the rich have benefitted more. People residing in Vientiane Capital, those living in urban areas, those belonging to the top quintile, and the Lao-Tai ethnic group obtained higher growth rates of per capita consumption. Access to electricity network significantly enhanced the growth of consumption, indicating the importance of infrastructure in moving out of poverty.